Disclosure of Non-financial Material Sustainability Information: Evidence from Australian Listed Companies in the Materials Sector - Al Mamun, Ashraf (Asian Business Review, 2019)
The broad objective of this paper is to measure the extent of disclosure of non-financial material sustainability information by Australian companies in the materials sector based on the GRI G4 guidelines. GRI G4 guidelines on economic, environmental, and social performance indicators are used based on 2014 and 2015 data to establish what constitutes non-financial material sustainability information by ASX listed Australian companies in the materials sector. The aggregate non-financial material sustainability disclosure is low for all companies in the materials sector. The findings show that a great degree of variation in sustainability disclosures exists among the listed Australian companies in the materials sector based on GRI G4 guidelines. The pattern of disclosure is similar for small-cap and medium-cap companies and they disclose less non-financial material sustainability information than large-cap companies. The sustainability score increased slightly in 2015 compared to 2014 for all companies and subgroup of companies based on market capitalization in aggregate as well as in economic, environmental, and social categories. JEL Classification Code: Q56 Funding Acknowledgement: This study is funded by the “Australian Government Research Training Program (RTP) Scholarship”.